PUTUSAN HAKIM AGAMA DALAM MASALAH CERAI GUGAT PADA SUAMI YANG TIDAK MEMBERI NAFKAH PRESPEKTIF HUKUM POSITIF DAN HUKUM ISLAM: PUTUSAN HAKIM AGAMA DALAM MASALAH CERAI GUGAT PADA SUAMI YANG TIDAK MEMBERI NAFKAH PRESPEKTIF HUKUM POSITIF DAN HUKUM ISLAM - Fita Firdausiyah (Al-Hukmi : Jurnal Hukum Ekonomi Syariah dan Keluarga Islam, 2023)
PUTUSAN HAKIM AGAMA DALAM MASALAH CERAI GUGAT PADA SUAMI YANG TIDAK MEMBERI NAFKAH PRESPEKTIF HUKUM POSITIF DAN HUKUM ISLAM Oleh: Vita Firdausiyah Vitalovers92@gmail.com Dosen Fakultas Syari’ah Universitas Islam Zainul Hasan ABSTRACT In a marriage bond, many husbands and wives have not even carried out their rights and obligations in accordance with applicable laws or regulations, where problems that often arise in a marriage that often causes wives to file for divorce from their husbands are none other than because the husband does not provide support to the husband. wife, therefore this case is the most common case in the Kraksaan Religious Court after the marriage dispensation, therefore the author wants to discuss how the religious judge's decision in the matter of divorce is sued for husbands who do not provide a living in the Kraksaan religious court from the perspective of Islamic law and positive law. Problem Formulation (1) What is the procedure for filing a lawsuit at the Kraksaan Religious Court? (2) How are Positive Laws and Islamic Laws Review of Religious Judges' Decisions on Divorce and Lawsuits for husbands who do not provide a living? This study aims to identify the procedures for filing for divorce at the Kraksaan Religious Court, and to find out the positive legal review and Islamic law on the decision of the Religious Judge in the Divorce Lawsuit issue for husbands who do not provide a living at the Kraksaan Religious Court. The research method used is qualitative / field research (field research) where this research is descriptive. Methods of data collection is done through observation, and interviews. Sources of data used come from primary data and secondary data. Analysis of the data used is qualitative data analysis with an inductive approach to thinking. It was concluded that the procedure for carrying out a lawsuit at the Kraksaan Religious Court must meet the requirements, including a marriage book and ID card, and the religious judge's decision on divorce lawsuits for husbands who do not provide a living from the perspective of Islamic law and positive law based on existing laws and regulations. , in Islamic law that is paying attention to qoidah fiqhiyyah and also in the Qur'an surah al Baqoroh verse 229 if it is worried that the two of them cannot carry out Allah's laws, the wife is not guilty of redeeming herself to her husband so that she can be separated from her husband. And based on positive law, namely Law Article 19 letter (f) PP Number 9 of 1975, Complications of Islamic Law Article 116 (f). And the procedure for filing for divorce at the Kraksaan Religious Court is in accordance with litigation procedures in Indonesia, like all decisions The Kraksaan Religious Court for example in the determination of the Kraksaan Religious Court Number: 115/Pdt.G/2021/PA.Krs, 106/Pdt.G/2021/PA.Krs, and Number: 339/Pdt.G/2021/PA.Krs. Key words: Positive Law, Islamic Law, Judge's Decision, Divorce